EVIDENCES OF SCIENTIFIC MIRACLE OF AL-QURâAN IN THE MODERN ERA - Sayska, Dwi Sukmanila; Arni, Jani (Jurnal Ushuluddin, 2016)
One of the miracles of al-Qurâan is iâjaz ilmi, itâs meant the information of al-Qurâan about science which is then able revealed and proven in accordance with the development of science. Iâjaz ilmi does not present itself, but should be explored and researched, so that the evidence of iâjaz ilmi can be more and more and grow over time. Scientists gave the parable is like a spring that never runs dry. Every time always comes new discoveries and scientific provisions which already hinted at al-Qurâan for 14 centuries ago as evidence of iâjaz. Iâjaz ilmi later became a effective propaganda media, especially among scientists. Many cases found confession of scientists when they were able to prove the truth of which is informed by al-Qurâan. In addition, evidence of ilmi iâjaz is able to ward off external oblique view of Islam that al-Qurâan is man work, because when they know that what is described by al- Qurâan has been proved by modern scientific discoveries, and eventually they acknowledges that al-Qurâan is really the word of God